Modelling the Factors Measuring Customer Service Excellence for Mobile Application Technology Usage in Abu Dhabi - Azlina Binti Md Yassin; Al Naqbi, Saeed (International Journal of Sustainable Construction Engineering and Technology, 2022)
In many areas of business, technological innovation is critical. The ability to use technology to transform organisations is now a requirement in all industries. Nonetheless, technological acceptance has a significant impact on overall corporate performance. Mobile applications are becoming more popular all over the world. As a result, the goal of this research is to look into the technology acceptance model in order to improve customer service in mobile applications. A questionnaire survey was used to collect data from mobile users in Abu Dhabi Municipality. The Partial Least Squares-Structural Equation Modelling (PLS-SEM) technique, aided by SmartPLS software, was used to analyse 396 completed questionnaire forms. The study’s findings indicate that perceived usefulness, perceived ease of use, and attitude all have a significant impact on the intention to use technology. The role of intention to use as a moderator is also confirmed, as is the moderating effect of user experience. Furthermore, statistical evidence supports the role of user experience as a moderator in the customer satisfaction experience. The study’s findings give marketing managers and academics a much stronger foundation for recommending CSE strategies. As a result, telecom operators must go above and beyond to improve PU, PEOU, and attitude, as well as develop strategies, in order to achieve a higher level of CSE.